Pengaruh Kesehatan Bank Dengan Menggunakan Pendekatan Risk Based Bank Rating (RBBR) Terhadap Penyaluran Kredit Pada Bank BUMN Periode 2013-2019 - Pingkan Aprilia Maramis; Jeifer Juandy Livingstone Rompas; Kristi Karla Arina (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to determine the effect of bank health using the RBBR approach on state-owned bank credit distribution for the 2013-2019 period. Indonesian Banking Statistics released by the Financial Services Authority noted that the amount of credit from Government-Owned Banks in September 2017 dominated the banking credit market share. Government-owned banks registered with BUMN are Bank Mandiri, BRI, BNI and BTN. Providing bank credit is one of the main bank activities in generating profits, but the biggest risk in banks also comes from providing credit. Based on Bank Indonesia Regulation no. 13/PBI/1/2011 concerning Assessment of the health level of a bank is carried out using a risk-based approach, namely Risk Based Bank Rating (RBBR) with assessment coverage of four factors, namely Risk Profile, GCG, Earnings and Capital. The analytical method used is descriptive analysis and multiple linear regression. The research results show that of all the four factors assessed using RBBR, only liquidity risk provides a